Accuracy of predictive equations in guiding tracheal intubation depth in children: A prospective study. Issue 12 (30th September 2021) - Khanna, Puneet; Garg, Heena; Ray, Bikash Ranjan; Singh, Ajay; Kundu, Riddhi; Sinha, Renu
Abstract: Background: Accurate insertion depth of endotracheal tube (ETT) in children has been predicted using the demographic variables, such as age, weight, and height. Middle finger length showed good correlation with ETT depth measurement in children aged 4–14 years. Aims: The primary objective was to correlate the actual ETT insertion depth with the depth derived from middle finger length, age, weight, and height formulae in children aged 1–4 years. The secondary objective was to find the most accurate formula for prediction of ETT insertion depth. Methods: This prospective parallel group study was done in 50 american society of anesthesiologists 1 or 2 children aged 1–4 years undergoing elective surgery under general anesthesia. Children with difficult airway, finger anomalies, or syndromic associations were excluded. Age, weight, height, and middle finger length of all children were measured. Depth of orally inserted uncuffed ETT and tracheal length was measured by fiberoptic bronchoscopy. The actual ETT depth was correlated with the depth calculated from different formulae. Results: The mean middle finger length was 4.42 ± 0.50 cm, age was 2.64 ± 1.07 years, weight was 12.28 ± 2.84 kg, and height was 82.89 ± 16.23 cm. The mean tracheal length was 6.42 ± 0.96 cm. The mean depth of ETT was actual depth (12.89 ± 1.09 cm), middle finger depth (13.23 ± 1.53cm; p = .001; 95%CI 0.12–0.50), age‐based depth 1(3.31 ± 0.53 cm; 95%CI 0.37–1.44; p = .001), weight‐based depth (14.14 ± 1.42 cm; 95% CI 0.10–0.51; p = .004), and height‐based depth (13.73 ± 0.94 cm; 95% CI 0.15–0.77; p = .004). Middle finger length and age‐based formulae showed higher number of accurate placements (58% each). Weight‐ (74%) and height (64%)‐derived formulae gave a higher number of distal ETT placements. Conclusion: Formulas based on the demographic variables and middle finger length showed good correlation with the actual ETT depth in children aged 1–4 years. The percentage of accurate ETT depth placements was higher with middle finger length and age‐based formulae.